Identidade sociomoral, modelos sociais e socialização dos valores - Susana Gonçalves (Universidade do Minho, 2013)
The paper introduces a psychosocial study about values, attitudes and behaviours of college students. A sample of 860 participants answered a questionnaire whose purposes where, among others, to clarify the impact of formal and informal educational experiences on social identity in university students. The research methodology will be presented and part of the results shown and discussed. Reported data are centred at the non-behavioural sphere of morality, namely the representation of good and excellence and the beliefs about self and worldviews. Students where inquired about their social models of excellence, i.e., people who excel and which the subject considers exemplar, due to his/her words and behaviours. Content analyses made it possible to catalogue the characteristics considered as criteria to judge a person as a model to be followed. This leads to the inference of student's social values. Results show that the patterns of sociomoral excellence are uninfluenced by the college experience. Other socialization processes, particularly those evolving at the family sphere, such as the educational style of parents, are much more influential upon social and moral beliefs and values of the student. Gender is another factor revealing significant effects.